2015
DOI: 10.1108/mf-12-2014-0310
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian revolution and stock market volatility: evidence from FIEGARCH model

Abstract: Purpose – Previously elaborated research works, dealing with the political uncertainty effect on stock market, have been primarily concerned with such political events as terrorist attacks, elections, wars, natural catastrophes and financial crashes. Such little research has been concerned with civil uprisings and revolutionary movements, as crucial sources of political uncertainty. The purpose of this paper is to study the impact of political uncertainty (resulting from the Tunisian Revolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 48 publications
(43 reference statements)
2
18
0
1
Order By: Relevance
“…In sum, there is no doubt that Arab Spring revolution in Tunisia, Egypt, Libya, Yemen and Syria affect macroeconomic variables and stock markets in the national economy and our results confirm those of Suleman (2012), Essaddam and Mnasri (2015), Mnasri and Nechi (2016) and Jeribi et al(2016) who show that terrorist attacks have a positive and significant impact on financial market volatility.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In sum, there is no doubt that Arab Spring revolution in Tunisia, Egypt, Libya, Yemen and Syria affect macroeconomic variables and stock markets in the national economy and our results confirm those of Suleman (2012), Essaddam and Mnasri (2015), Mnasri and Nechi (2016) and Jeribi et al(2016) who show that terrorist attacks have a positive and significant impact on financial market volatility.…”
Section: Resultssupporting
confidence: 83%
“…Little research has been done on the impact of political uncertainty stemming from civil uprisings (eg the Tunisian revolution) on the stability and characteristics of stock market cycles. So, Jeribi et al (2016) study the impact of political uncertainty (resulting from the Tunisian revolution) on the volatility of the main sector in stock market indices of the Tunisian Stock Exchange. The authors apply the fractionally integrated exponential generalized autoregressive conditional heteroscedasticity model (FIEGARCH).…”
Section: Stock Market Reaction To Political Uncertaintymentioning
confidence: 99%
“…Moreover, the author revealed that the impact of bad news on stock markets volatility is higher than that of the impact of good news. The same results of negative influences of Arab Spring had been observed by Mnif (2017) and Jeribi et al (2015) in Tunisian stock markets.…”
Section: The Impact Of Political Instability On Stock Marketssupporting
confidence: 82%
“…The activities of the Tunis stock exchange were hardly affected following the 2011 revolution; the benchmark index TUNINDEX 2 saw its largest cumulative decline at 21% before recovering for the rest of the year and finishing 2011 with a lower value of 7.6% 3 . Tunisian 2011 experiment turns out to have a very crucial impact on the Tunisian stock market (Jeribi, Jarboui & Fakhfekh, 2015). Unfortunately, the political uncertainty, as manifested by instable financial market and sluggish economy, could shake the confidence of national and international investors.…”
Section: Introductionmentioning
confidence: 99%